Quantitative Characterization of High-Touch Surfaces in Emergency Departments and Hemodialysis Facilities - Wang, Tina; Barofsky, Alana; Simon, Matthew; Saiman, Lisa; Furuya, E. Yoko; Calfee, David (Infection control and hospital epidemiology, 2020)
Background: The healthcare environment can serve as a reservoir for many microorganisms and, in the absence of appropriate cleaning and disinfection, can contribute to pathogen transmission. Identification of high-touch surfaces (HTS) in hospital patient rooms has allowed the recognition of surfaces that represent the greatest transmission risk and prioritization of cleaning and disinfection resources for infection prevention. HTS in other healthcare settings, including high-volume and high-risk settings such as emergency departments (EDs) and hemodialysis facilities (HDFs), have not been well studied or defined. Methods: Observations were conducted in 2 EDs and 3 HDFs using structured observation tools. All touch episodes, defined as hand-to-surface contact regardless of hand hygiene and/or glove use, were recorded. Touches by healthcare personnel, patients, and visitors were included. Surfaces were classified as being allocated to individual patients or shared among multiple patients. The number of touch episodes per hour was calculated for each surface to rank surfaces by frequency of touch. Results: In total, 28 hours of observation (14 hours each in EDs and HDFs) were conducted. 1,976 touch episodes were observed among 62 surfaces. On average, more touch episodes were observed per hour in HDFs than in EDs (89 vs 52, respectively). The most frequently touched surfaces in EDs included stretcher rails, privacy curtains, visitor chair arm rests and seats, and patient bedside tables, which together accounted for 68.8% of all touch episodes in EDs (Fig. 1). Frequently touched surfaces in HDFs included both shared and single-patient surfaces: 27.8% and 72.2% of HDF touch episodes, respectively. The most frequently touched surfaces in HDFs were supply cart drawers, dialysis machine control panels and keyboards, handwashing faucet handles, bedside work tables, and bed rail or dialysis chair armrests, which accounted for 68.4% of all touch-episodes recorded. Conclusions: To our knowledge, this is the first quantitative study to identify HTSs in EDs and HDFs. Our observations reveal that certain surfaces within these environments are subject to a substantially greater frequency of hand contact than others and that a relatively small number of surfaces account for most touch episodes. Notably, whereas HTSs in EDs were primarily single-patient surfaces, HTSs in HDFs included surfaces shared in the care of multiple patients, which may represent an even greater risk of patient-to-patient pathogen transmission than single-patient surfaces. The identification of HTSs in EDs and HDFs contributes to a better understanding of the risk of environment-related pathogen transmission in these settings and may allow prioritization and optimization of cleaning and disinfection resources within facilities. Funding: None Disclosures: None